COMPLICATIONS OF ASCARIASIS - M. Bajoghli; T.S. Ajodani; H. Azami; A. Soheilian (Tehran University of Medical Sciences, 1976)
Three-year-old boy came to emergency room of Soraya Medical Center with abdominal pain, nausea, vomiting and distended abdomen for a period of three days. X-ray showed fluid in the peritoneal cavity and at pleural space, mild elevation of the hemi diaphragm, and thick left diaphragm. Surgery showed sub diaphragmatic abscess under in the hemi diaphragm and peritonitis. The autopsy showed several abscesses in the liver with several Ascaris on them. There was perforation of the abscess from the superior aspect of the liver into in to the cavity.